2009
DOI: 10.1111/j.1749-6632.2009.04673.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Serologies and Autoantibodies in Inflammatory Bowel Disease

Abstract: The aim of this study was to reevaluate the role of infection in inflammatory bowel disease (IBD). Sera from 119 patients with IBD [80 with Crohn's disease (CD); 39 with ulcerative colitis] and 98 healthy controls were assessed using the Bio-Rad BioPlex 2200 for the presence of Toxoplasma gondii, cytomegalovirus, Epstein-Barr virus, Treponema pallidum, and Saccharomyces cerevisiae. Hepatitis B virus, hepatitis C virus (HCV), and anti-Helicobacter pylori antibodies were assessed by ELISA. In addition, sera were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 35 publications
(56 reference statements)
4
46
0
4
Order By: Relevance
“…Second, we found a lower prevalence of antihepatitis B antibodies among patients with MS and SLE [6]. Third, we detected a low prevalence of H. pylori seropositivity among patients with IBD [10], which is in agreement with other studies that showed that H. pylori seropositivity was associated with late presentation of IBD [81].…”
Section: The Protective Dialogue Between Infections and Autoimmunitysupporting
confidence: 91%
See 1 more Smart Citation
“…Second, we found a lower prevalence of antihepatitis B antibodies among patients with MS and SLE [6]. Third, we detected a low prevalence of H. pylori seropositivity among patients with IBD [10], which is in agreement with other studies that showed that H. pylori seropositivity was associated with late presentation of IBD [81].…”
Section: The Protective Dialogue Between Infections and Autoimmunitysupporting
confidence: 91%
“…In recent years, the compound interplay between infections and autoimmunity has been studied extensively. Here, we summarize the current literature and preliminary results from our international study on this issue [4][5][6][7][8][9][10][11][12][13] (Figure 1). The versatile interactions of ADs with different infectious agents, the burden of infections from childhood to adulthood, immune and genetic mechanisms, and the possibility that infections also confer protection from autoimmunity are also discussed (Box 1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the association between the intensity of expression in the intestinal mucosa and the severity of the IBD inflammation, viral replication was also found in healthy mucosa [96] . A higher CMV infection rate was not observed in the IBD population with respect to the general population [97] .…”
Section: Citomegalovirusmentioning
confidence: 61%
“…98 Interestingly, H. pylori DNA suppresses the production of IL-12 and type 1 IFN by mouse bone marrow-derived DCs and human plasmacytoid DCs and attenuates the severity of the inflammatory response in dextran sodium sulfate-induced colitis, 99 suggesting a partial explanation for the inverse association between H. pylori infection and inflammatory bowel disease. [100][101][102] To dissect the interaction between DCs and Tregs, investigators have elegantly shown that H. pylori reprogram DCs to a tolerance-promoting phenotype in an IL-18-dependent manner, thereby promoting Tregs and suppressing effector T cell function. 103 Subsequently, H. pylori γ-glutamyl transpeptidase and VacA were shown to drive the DC-induced Treg skewing.…”
mentioning
confidence: 99%